DISSOLUTION OF PARLIAMENT – LEGAL NATURE OF THE DISSOLUTION ACT AND POSSIBILITIES OF CONTROL - Cvetkovic, Aleksandar (National interest, 2024)
The subject of this paper is the examination of the legal nature of the dissolution act and the consideration of the possibilities for controlling such an act. Dissolution, as a characteristic of the parliamentary system of government, is traditionally viewed as a political act, which implies that it is not subject to legal control. This paper reexamines this firmly rooted position in our legal theory on two levels. The first part of the paper discusses two cases of the power of the Bundestag’s dissolution before the Federal Constitutional Court of Germany. The second part, drawing on Germany’s experience and particularly considering the practice of dissolution in Serbia, critically analyzes the constitutional provisions of this institute. A special section is dedicated to analyzing relevant constitutional and legal provisions regarding whether the Constitutional Court of Serbia can control the act of dissolution. In addition to strict legal analysis, the paper also examines the justification of such possible actions. Предмет овог рада је испитивање правне природе акта о распуштању и разматрање могућности контроле таквог акта. Распуштање као одлика парламентарног система власти традиционално се посматра као политички акт из чега произлази да не подлеже правној контроли. Такав, у нашој правној теорији врло чврсто укорењен став, у овом раду се преиспитује на два нивоа. У првом делу рада се разматрају два случаја контроле распуштања Бундестага пред Савезним уставним судом Немачке. У другом делу се са ослонцем на искуство Немачке, а нарочито узимајући у обзир праксу распуштања у Србији, критички анализирају уставна решења тог института. Посебан део чини анализа релеватних уставних и законских решења о о томе да ли Уставни суд може да контролише акт о распуштању. Поред строго правне анализе, посебно се разматра и питање оправданости таквог могућег поступања.